First comes like : a novel - Rai, Alisha (Avon, an imprint of HarperCollinsPublishers, 2021)
"Beauty expert and influencer Jia Ahmed has her eye on the prize: conquering the internet today, the entire makeup industry tomorrow, and finally, finally proving herself to her big opinionated family. She has little time for love, and even less time for the men in her private messages--until the day a certain international superstar slides into her DMs, and she falls hard and fast. There's just one wrinkle: he has no idea who she is. The son of a powerful Bollywood family, soap opera star Dev Dixit is used to drama, but a strange woman who accuses him of wooing her online, well, that's a new one. As much as he'd like to focus on his Hollywood fresh start, he can't get Jia out of his head. Especially once he starts to suspect who might have used his famous name to catfish her..."--